COOPERATIVE MODEL IMPLEMENTATION OF STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) METHODS FOR INCREASING INTEREST AND SOCIOLOGY OF LEARNING OUTCOMES FOR CLASS X.2 BATIK 1 HIGHSCHOOL SURAKARTA 2012/2013 ACADEMIC YEAR - PRATIWI, YOFITA KHAIRUNISA (SOSIALITAS; Jurnal Ilmiah Pend. Sos Ant)
ABSTRACT Yofita Khairunisa Pratiwi. K8409073. COOPERATIVE MODEL IMPLEMENTATION OF STAD (STUDENT TEAM ACHIEVEMENT DIVISIONS) METHODS FOR INCREASING INTEREST AND SOCIOLOGY OF LEARNING OUTCOMES FOR CLASS X.2 BATIK 1 HIGHSCHOOL SURAKARTA 2012/2013 ACADEMIC YEAR. Thesis, Surakarta: The Faculty of Teaching and Education Sebelas Maret University. Juny 2013.The purpose of this research is to increase the interest and achievement in Sociology learning for class x.2 Batik 1 highschool Surakarta by applying the Student Team Achievement Divisions learning model. This research is a class action research. The research was conducted in two cycles, with each cycle consisting of planning, action, observation, and reflection. The subjects were class x.2 Batik 1 highschool Surakarta which amounts to 38 students. Source of data comes from teachers and students. The data collection techniques is by observation, questionnaires, tests, and documentation or archives. The validity of the data using source triangulation techniques. Data analysis using the comparative descriptive analysis techniques.The results showed that class x.2 Batik 1 highschool Surakarta student achievement in sociology subjects had increased after the implementation of the Student Team Achievement Divisions learning model. This is indicated by an increase in average interest of each cycle. Average student interest before any action is taken on indicator only 2.58 on attention, 3.02 on the relevance, 2.09 on confidence and at 2.12 against complacency. Once applied the action on the first and second cycle average student interest has increased in each of the indicators, the first and second cycle students' attention increased to 3.07 and increased to 3.56, relevance increased to 3.23 then to 4.66 in the second cycle, student confidence increased to 2.38 and increased to 3.67 in cycle II, and student satisfaction also increased to 2.42 in the first cycle and the second cycle to 4.57. Student learning outcomes also improved, as shown by an increase in average student learning outcomes in each cycle. Average student learning outcomes before the action only (8.57%) 64.42, after application of the action in the first cycle average student learning outcomes increased to (68.42%) 73.82. In the second cycle the average student learning outcomes increased to (76.32%) 79.34.The research conclusion is application of Student Team Achievement Divisions learning model can increase the interest and learning outcomes of sociology subjects of class x.2 Batik 1 highschool Surakarta student. Keywords: STAD cooperative learning, learning interest, learning outcome